Phase Constituents Modeling in Hybrid Multi-Component High-Boron Alloy - Chabak, Yu.G.; Golinskyi, М.А.; Efremenko, V.G.; Shimizu, К.; Halfa, H.; Zurnadzhy, V.І.; Efremenko, B.V.; Kovbasiuk, Т.М. (Physics and Chemistry of Solid State, 2022)
The present work is focused on analyzing the thermodynamically equilibrium path of structure formation in a multi-component Fe-W-Mo-Cr-Ti-Mn-Si alloy of tribotechnical purpose, containing 0.72 wt. % C and 2.75 wt. % B is analyzed. Computer simulation of the crystallization process was performed using the program “Thermo-Calc Software”. It was found that the alloy belongs to the hyper-eutectic compositions, since its crystallization begins at 1472 oC with the formation of primary boride WB and carbide TiC. After a series of subsequent eutectic reactions (in the range of 1126-923 oC) and solid-phase transformations, a set of equilibrium phases is formed in the alloy, which at room temperature consists of borides WB, MoV, Fe2B, Cr4B, Mn4B, carbides TiC, M7C3, and ferrite. The total volume fraction of borides and carbides is 45.05 vol. %. A comparison of the obtained data with the results of the study of the manufactured alloy showed that the simulation with “Thermo-Calc Software” provides satisfactory adequacy in predicting the structure in the alloys of the selected alloying system.